Pentatricopeptide Repeat Gene-Mediated Mitochondrial RNA Editing Impacts on Rice Drought Tolerance - Luo, Zhi; Xiong, Jie; Xia, Hui; Wang, Lei; Hou, Guihua; Li, Zhaoyang; Li, Jing; Zhou, Hengling; Li, Tianfei; Luo, Lijun (Frontiers in Plant Science, 2022)
Mitochondrial RNA editing plays crucial roles in the plant development and environmental adaptation. Pentatricopeptide repeat (PPR) genes, which are involved in the regulating mitochondrial RNA editing, are potential gene resources in the improvement of rice drought tolerance. In this study, we investigated genome-wide mitochondrial RNA editing in response to drought between upland and lowland rice. Responses of mitochondrial RNA editing to drought exhibit site-specific and genotype-specific patterns. We detected 22 and 57 ecotype-differentiated editing sites under well-watered and drought-treated conditions, respectively. Interestingly, the RNA editing efficiency was positively correlated with many agronomic traits, while it was negatively correlated with drought tolerance. We further selected two mitochondrial-localized PPR proteins, PPR035 and PPR406, to validate their functions in drought tolerance. PPR035 regulated RNA editing at rps4-926 and orfX-406, while PPR406 regulated RNA editing at orfX-355. The defectiveness in RNA editing at these sites had no apparent penalties in rice respiration and vegetative growth. Meanwhile, the knockout mutants of ppr035 and ppr406 show enhanced drought- and salt tolerance. PPR035 and PPR406 were under the balancing selection in upland rice and highly differentiated between upland and lowland rice ecotypes. The upland-dominant haplotypes of PPR035 and PPR406 shall contribute to the better drought tolerance in upland rice. They have great prospective in the improvement of rice drought tolerance.